Study the Toxicity and Anticancer activity of Some New Amic Acid and Their Derivatives of Mefenamic acid - Ali A. Sabah1, Muna S. Al-Rawi1, Jumbad H. Tomma1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
A series of amic acid derivatives of mefenamic acid were synthesized with the aim of inhibitting topical gastrointestinal toxicity of mefenamic acid. The key intermediate amic acid (III) was prepared from the reaction of acid hydrazid of mefenamic acid(II) with phthalic anhydrides in dry actone. The new type of imide compound (IV) was dehydrated the amic acid(III) with acetic anhydrous and sodium acetate. The esterification of hydroxyl groups of amic acid (III) produce corresponding ester(V), which was condensed with hydrazine hydrate to give acid hydrazide (VI), then the later compound reacted with syringaldehyde in dry benzene to yield new schiff base (VII). The new derivatives containing heterocyclic unit (VIII)-(X), four and five, member ring were successfully formed such as azetidin-2-one, thiazolidin-4-one, and,imidazolidin-4-one. The structures of the synthesized compounds were confirmed using FTIR, 1HNMR, Mass and CHN-S. The antibacterial activities of some synthesized compounds were screened and showed a highest or low inhibition against Staph.aureus (G+), Bacillus subtilisa (G+), Klebsiella pneumoniae (G-), and E.coli (G-). Also, The cytotoxic effect of different concentrations of some the synthesized compounds was tested against MCF-7 cell line (human breast carcinoma cells) and positive results were obtained for some of them, which encouraged us to study the toxicity using living organisms (mice) to evaluate its acute toxicity and proved the resules of non-toxicity of the derivatives.